Path analysis reveals cross-country differences between Czech and Chinese university students in effect of internet and smartphone addiction, mental health, and personality traits on academic achievement in the post-pandemic era - Kvintova, Jana; Novotny, Jan Sebastian; Liu, Hongyang; Vachova, Lucie; Kantor, Jiri (BMC psychology, 2024)
Despite extensive evidence on the impact of various mental health issues including smartphone/internet addiction, and personality traits on academic achievement, little is known about the complex interactions between multiple of these factors simultaneously, as well as cross-country differences in these nuanced relationships. In particular, understanding the role of the mentioned addictions has become increasingly important in recent years in the context of the COVID-19 pandemic. The aim of this cross-country study was to investigate, using path analysis, the complex relationships between mental health determinants (depression, anxiety, stress, resilience, and smartphone/internet addiction) and academic achievement in 1785 Czech and Chinese university students using an online battery of psychological tests. The results confirmed the previously described effect of multiple factors (anxiety, stress, resilience, smartphone/internet addiction, personality traits, and sex, Extraversion, Agreeableness, Conscientiousness) on academic achievement, overlapping in most cases for both groups of students. At the same time, however, different country-dependent patterns of interactions emerged. For the Czech students, the variables formed a complex network of interacting factors, whereas for the Chinese students, the effect of each cluster of factors was separate for individual domains of academic achievement. These cross-country differences have implications particularly for planning and targeting the most effective interventions to promote and develop academic achievement.
Keywords: Male; chytrý telefon; Cross-Cultural Comparison; Smartphone; China; návykové chování; školní úspěšnost; Academic achievement; netholismus; Humans; Internet Addiction Disorder; osobnost; Smartphone addiction; úzkost; Internet addiction; Czech Republic; Česká republika; mužské pohlaví; Female; COVID-19; mladiství; Anxiety; Behavior, Addictive; duševní zdraví; Personality; deprese; Cross-country differences; Personality traits; srovnání kultur; Mental health; Students; ženské pohlaví; Čína; Mental Health; univerzity; mladý dospělý; Young Adult; Adult; Academic Success; Depression; Adolescent; lidé; dospělí; studenti; Universities